Epidermoid cyst in the parotid region. A case report and review of the literature - Gómez Hernández, Kevin Andrew (2021)
Epidermoid cysts are benign cystic lesions that develop from abnormal epithelial components of ectodermal tissue formed during the fetal period (congenital) or from epithelium implanted after surgery or trauma (acquired). The epidermoid cyst is considered a benign lesion that usually affects the scalp, face, neck, back, and torso. 7% of these cysts occur in the head and neck, whereas the oral cavity represents only 1.6%. A clinical case is presented with a histopathological diagnosis of an epidermoid cyst in the parotid region, which did not present compromise of the glandular parenchyma, that was treated with complete surgical excision, without alteration or damage to the facial nerve, with a three-year postoperative follow-up without recurrence.